Optical Thermography Infrastructure to Assess Thermal Distribution in Critically Ill Children - Monisha Shcherbakova; Rita Noumeir; Michael Levy; Armelle Bridier; Victor Lestrade; Philippe Jouvet (IEEE Open Journal of Engineering in Medicine and Biology, 2022)
The temperature distribution at the skin surface could be a useful tool to monitor changes in cardiac output. Goal: The aim of this study was to explore infrared thermography as a method to analyze temperature profiles of critically ill children. Methods: Patients admitted to the pediatric intensive care unit (PICU) were included in this study. An infrared sensor was used to take images in clinical conditions. The infrared core and limb temperatures (θc & θl) were extracted, as well as temperatures along a line drawn between these two regions. Results: The median [interquartile range] θc extracted from the images was 33.88°C [32.74-34.19] and the median θl was 30.21°C [28.89-33.13]. There was a good correlation between the θc and the clinical axillary temperature (rho = 0.39, p-value = 0.016). There was also a good correlation between the θc and θl (rho = 0.66, p-value = 1.2 e−05). Conclusion: Thermography was found to be effective to estimate the body temperature. Correlation with specific clinical conditions needs further study.